2020
DOI: 10.1093/bjsopen/zraa003
|View full text |Cite
|
Sign up to set email alerts
|

Single-use negative-pressure wound therapy versus conventional dressings for closed surgical incisions: systematic literature review and meta-analysis

Abstract: Background Surgical-site complications (SSCs) remain a significant cause of morbidity and mortality, particularly in high-risk patients. The aim of this study was to determine whether prophylactic use of a specific single-use negative-pressure wound therapy (sNPWT) device reduced the incidence of SSCs after closed surgical incisions compared with conventional dressings. Methods A systematic literature review was performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
(22 reference statements)
0
17
1
3
Order By: Relevance
“…This was also suggested in previous similar meta-analysis studies, which showed a similar effect of negative pressure wound therapy and conventional wound dressings in subjects with different types of orthopaedic trauma surgery. [32][33][34][35][36][37][38][39][40] The insignificant results of negative pressure wound therapy in the length of hospital stay also need additional study and clarification because no clear reasoning was found to clarify these outcomes. Wellconducted studies are also required to measure these factors and the blend of different ages and ethnicity, because our meta-analysis study could not answer whether they are related to the outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…This was also suggested in previous similar meta-analysis studies, which showed a similar effect of negative pressure wound therapy and conventional wound dressings in subjects with different types of orthopaedic trauma surgery. [32][33][34][35][36][37][38][39][40] The insignificant results of negative pressure wound therapy in the length of hospital stay also need additional study and clarification because no clear reasoning was found to clarify these outcomes. Wellconducted studies are also required to measure these factors and the blend of different ages and ethnicity, because our meta-analysis study could not answer whether they are related to the outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The devices that were used in breast surgery, PREVENA and PICO, have been widely adopted by other surgical subspecialties including orthopaedic, gynaecological, colorectal, and vascular [ 17 ]. The application of CINPT has the potential to reduce post-operative SSI by 63% and reduce the length of hospital stay [ 18 ]. Despite this evidence, its use in breast surgery remains low and far between, with very limited evidence regarding its use.…”
Section: Reviewmentioning
confidence: 99%
“…Dabei ist der durchgehende Tenor zunehmend positiv. Während die Studienergebnisse initial noch uneinheitlich waren [22], zeigen mittlerweile verfügbare, aktuelle Metaanalysen über mehrere chirurgische Disziplinen hinweg insbesondere bei Risikopatienten und zur Reduktion postoperativer Wundinfektionen eine signifikante Reduktion der Infektionsraten im Vergleich zur Standardtherapie [30,34]. Dabei erzielten die analysierten RCTs eine signifikante Reduktion der postoperativen Wundinfektionsrate um 5 bis 8 Prozentpunkte und die Metaanalyse von Saunders et al identifizierte eine "Number needed to treat" von 20 [4,34].…”
Section: Wundeunclassified
“…Während die Studienergebnisse initial noch uneinheitlich waren [22], zeigen mittlerweile verfügbare, aktuelle Metaanalysen über mehrere chirurgische Disziplinen hinweg insbesondere bei Risikopatienten und zur Reduktion postoperativer Wundinfektionen eine signifikante Reduktion der Infektionsraten im Vergleich zur Standardtherapie [30,34]. Dabei erzielten die analysierten RCTs eine signifikante Reduktion der postoperativen Wundinfektionsrate um 5 bis 8 Prozentpunkte und die Metaanalyse von Saunders et al identifizierte eine "Number needed to treat" von 20 [4,34]. Spezifisch für gefäßchirurgische Zugangswege und Operationen konnten aktuelle Studien und Metaanalysen mit signifikanter Reduktion der postoperativen Wundinfektionsrate für Leistenzugänge [5,18], periphere Bypasschirurgie [13], Majoramputationen [6] und generell vaskuläre Chirurgie [35,42] aus den letzten drei Jahren identifiziert werden.…”
Section: Wundeunclassified
See 1 more Smart Citation